Analysis of Students’ Thinking Processes in Chemistry Problem Solving: A Literature Review of Learning Difficulties in Senior High School - Purnomo, Vannesya Enriquetha; M. Muchson; Munzil (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
Chemistry learning difficulties among senior high school students often arise due to the abstract and hierarchical nature of chemical concepts, which require strong reasoning and problem-solving skills. These difficulties are closely related to students’ thinking processes when understanding concepts and solving problems. This study aims to analyze patterns of students’ thinking processes that contribute to learning difficulties, identify the stages where obstacles most frequently occur, and summarize recommended instructional strategies. This research used a descriptive qualitative literature review of 20 selected journal articles. The findings show that students’ thinking processes are generally unsystematic, as they tend to apply formulas without sufficient conceptual understanding. The most dominant obstacles occur at the conceptual and mathematical stages, followed by procedural and representational difficulties. Recommended strategies include diagnostic assessments, strengthening prerequisite concepts, contextual learning, and integration of multiple chemical representations.